The Influence of Production Costs, Working Capital, and Sales on Net Profit of Cosmetic Companies Listed on the IDX 2018–2023 - Bianca Oktavia; Edi Firdaus; Trustorini Handayani; Muhamad Nur Ramadhan; Reynaldhy Putra Herdiansyah (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This research investigates the impact of production costs, working capital, along with sales volume in relation to net profit in manufacturing companies within the cosmetics and household goods sub-sector registered on the Indonesia Stock Exchange for the period 2018 - 2023. This study employed a quantitative approach with descriptive and verification methods. By means of purposive sampling, five companies were selected, resulting in 30 observations over six years. Data analysis techniques include path analysis, classical assumption tests, correlation, coefficient of determination, and hypothesis testing, supported by IBM SPSS Statistics 20. The study demonstrates that production costs with working capital have insignificant and positive effect on net profit, while sales volume exhibits insignificant and negative effect. When tested simultaneously, all three variables show a positive but insignificant relationship with net profit. These results suggest that the profitability of companies in this subsector is not solely determined by production costs, working capital, along with sales volume, but is likely to be influenced by additional factors within and outside the organization beyond the scope of this study. Keywords: Production Costs; Working Capital; Sales Volume; Net Profit; Manufacturing Companies